LEXICAL AND SYNTACTIC AMBIGUITY IN HUMOR - Charina, Intan Nur (Sanata Dharma University, 2017)
Ambiguity occurs when a sentence has more than one meaning. Ambiguity can be caused by the ambiguous lexicon in which one word has more than one meaning and it can also be caused because of the way the sentence is structure (syntactic). The context also determines whether the sentence can be interpreted differently and become ambiguous. Ambiguity often causes confusion, and has become one of the phenomena in language studies, especially semantics. This study investigates ambiguity in creating humors. The data were taken from electronic sources in forms of newspaper headlines, jokes, riddles and anecdotes. The number of the data collection includes 25 cases of ambiguity. 12 sentences were lexically ambiguous, while the other 13 sentences were syntactically ambiguous. The results showed that lexical ambiguity and syntactic ambiguity were the language devices used to create puns in humor. The results also suggested that the ambiguity could be an effective source of humor when it particularly involves dual interpretations in which one interpretation gives a serious meaning and tone, whereas the other interpretation gives a humorous meaning which is not likely to occur in normal contexts.DOI: https://doi.org/10.24071/ijhs.2017.010113